Engagements (et) publics. Éléments pour une sociologie publique de la prison - Corentin Durand (Criminocorpus)
What is the role of social science research in the penitentiary or carceral field? The article proposes to address this classic question from the under-studied perspective of the diversity of the publics of the social sciences. If social sciences, through their ability to describe, to understand and to explain, provide grasps on the social world, it becomes critical to wonder who we are providing with these grasps to, and on what or on whom. In the light of Anglo-Saxon debates that have been structured over the last decade around the labels of public sociology and public criminology, this question is likely to stir new research, discussion and dissemination of the social sciences, as well as to question the social and political implications of our work in the penitentiary or carceral field.